On the long-run equilibrium value of Tobin's average Q - Rainer Franke; Boyan Yanovski (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2015)
This note considers Tobin's average Q in a framework where firms finance investment by equities and debt. The determination of its long-run equilibrium value Qo is based on positing equality of the loan rate and, adjusted for a risk premium, the return on equities. Qo can thus be characterized as a ratio of two rates representing the somewhat modified interest costs and profits of the firms. The familiar benchmark value Qo=1 obtains if another condition on the risk premium holds true, which may or may not be the case. An elementary numerical check demonstrates that possible deviations of Qo from unity are not overly dramatic.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: C02; D84; E12; E30; 330; Tobin's average Q; debt and equity financing; no-arbitrage condition; fundamentalist traders